Output of neurogliaform cells to various neuron types in the human and rat cerebral cortex - Oláh, Szabolcs; Komlósi, Gergely; Szabadics, János; Varga, Csaba; Tóth, Éva; Barzó, Pál; Tamás, Gábor (Frontiers in Neural Circuits, 2007)
Neurogliaform cells in the rat elicit combined GABAA and GABAB receptor-mediated postsynaptic responses on cortical pyramidal cells and establish electrical synapses with various interneuron types. However, the involvement of GABAB receptors in postsynaptic effects of neurogliaform cells on other GABAergic interneurons is not clear. We measured the postsynaptic effects of neurogliaform cells in vitro applying simultaneous whole-cell recordings in human and rat cortex. Single action potentials of human neurogliaform cells evoked unitary IPSPs composed of GABAA and GABAB receptor-mediated components in various types of inteneuron and in pyramidal cells. Slow IPSPs were combined with homologous and heterologous electrical coupling between neurogliaform cells and several human interneuron types. In the rat, single action potentials in neurogliaform cells elicited GABAB receptor-mediated component in responses of neurogliaform, regular spiking, and fast spiking interneurons following the GABAA receptor-mediated component in postsynaptic responses. In conclusion, human and rat neurogliaform cells elicit slow IPSPs and reach GABAA and GABAB receptors on several interneuron types with a connection-specific involvement of GABAB receptors. The electrical synapses recorded between human neurogliaform cells and various interneuron types represent the first electrical synapses recorded in the human cortex.